# Math

posted by .

Find (fog)(2)
f(x)=Squareroot 4-x; g(x)=1-3x^2

Find (gof)(-2) for the same problem.

• Math -

(fog)2 = f(f(2))
g(2) = 1 - 12 = -11
f(g(2) = f(-11) = √(4 -(-11)) = √15

do the second one in the same way

## Similar Questions

1. ### Algebra 2

If f(x) = x-3 g(x) = 2x+5 find fog and gof
2. ### Algebra help

Find (fog)(x)and (gof)(x)if f(x)=x-x^2 and g(x)= 2x+3.
3. ### Composite Functions

f(x)=(7x+28)/(x-3) and g(x)=(3x+28)/(x-7) Find: (fog)(x) (gof)(x) (fog)(-1)
4. ### Math

Find (fog)(2) and (gof)(-2) f(x)=Square root of 4-x; g(x)=1-3x^2 Show work.
5. ### math

Find (gof)(-2) f(x)=Squareroot of 4-x; g(x)=1-3x^2
6. ### math

Find a. fog b. gof c. fof d. gog f(x)=4-x g(x)=3x-5
7. ### math

Find a. fog b. gof c. fof d. gog for each function f(x)=4-x g(x)=3x-5
8. ### college algebra

1. answer the following for the given quadratic function f(x)=x^2+10x-11 a.what is the vertex (h,k) of f?
9. ### Algebra

If f(x)= ln x, g(x) = e^3x, and h(x) = x^7, find the following... a) (fog)(x) What is the domain of fog?
10. ### Maths

Let f(x)= 2x+1 and g(x) = 3x^2-4 find: a) f^-1 b) gof (-2) c) fog (x)

More Similar Questions